Public R&D funding and entrepreneurial innovation - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2008)
This study does not find any significant direct relationship between the public R&D funding and the firms' innovation output. The firms obtaining the public R&D support were not performing significantly better, on average, than others. However, we find evidence that the public R&D finance has substantially influenced the innovation output of the firms that have undertaken certain types of innovations activities. Particularly, public funding targeted to the firms focusing on new business areas in their R&D projects seems successful. Certain types of collaboration seem to also generate better entrepreneurial performance in terms of innovation. Those large firms that have more intensively collaborated with the SMS firm partners in their publicly funded R&D projects have filed more patent applications than other companies.
Keywords: L10; O33; O38; 330; innovation; public R&D subsidies; technology policy; Forschungs- und Technologiepolitik; Forschungssubvention; Betriebliche Forschung; Innovation; Wirkungsanalyse; Finnland